(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Multilateral diplomacy slowly but surely leads us to democratization of international society, developing its own machinery, techniques own characteristic "language" and professional ethics. The undoubtedly fact that multilateral diplomacy seeks to accomplish tasks that are of great importance to all of us as individuals, while achieving its greatest benefit among almost all international subjects, overcoming the differences between them, show us the benefits of multilateral diplomacy.